Efektivitas Layanan Perpustakaan Berbasis Inklusi Sosial di Perpustakaan Umum Daerah Kota Payakumbuh - Erlin, Ifany Putri; Nelisa, Malta (Lembaga Yasin AlSys, 2025)
This study aims to describe the services and effectiveness of the social inclusion-based library program at the Regional Public Library of Payakumbuh City. The research used a quantitative approach with saturation sampling techniques, involving 65 respondents who participated in social inclusion activities in 2024. The main instrument was a questionnaire that had been tested for validity and reliability. The results indicate that social inclusion services achieved a score of 1625 out of 5980 (93%), which falls into the